Atezolizumab for the treatment of breast cancer. (4th May 2018) - Basile, Debora; Pelizzari, Giacomo; Vitale, Maria Grazia; Lisanti, Camilla; Cinausero, Marika; Iacono, Donatella; Puglisi, Fabio
ABSTRACT: Introduction : Breast cancer (BC) is the most common cancer diagnosed among women. The development of new personalized therapeutic strategies has reshaped the landscape in this field. However, BC is still the first cause of death among women. Interestingly, several preclinical studies and some clinical evidences are focused their attention on the role of immune system and immunotherapy on cancer control, also in BC. Areas covered : Usually, BC has been considered a not immunogenic tumor for its low mutational load. However, recent studies have evidenced that some subtypes, triple negative and HER-2 positive BC, are 'hot' tumors, thus more immunogenic. Moreover, the presence of immune infiltrate is positively associated with favorable prognosis. Therefore, the use of immune-checkpoint inhibitors seems to be an encouraging treatment option also in BC. Among these drugs, atezolizumab is an anti-PD-L1 monoclonal antibody with a particular structure that reduce antibody-dependent cellular cytotoxicity against T cells, increasing quantitatively and qualitatively the effective response. Expert opinion : The use of immunotherapy is a promising option for BC. However, at the same time it still raises many doubts. Surely, the research and the validation of immune biomarkers can permit to identify patients who more benefit from these drugs.